PROGRAM KEMITRAAN UNIVERSITAS (PKU) BAGI KADER DI DESA DONOROJO MERTOYUDAN MAGELANG - Robiul Fitri Masithoh; Sigit Priyanto (LPPM UMRI, 2019)
The Cadres who handling the” Posyandu lansia “are still not exposed in the use of their own blood sugar level gauges so that they cannot detect in the patient's condition hypoglycemia or hyperglycemia. The purpose of this activity is to train, practice and assist cadres in using blood sugar levels in detecting elderly people with hypoglycemia or hyperglycemia in the village of Donorojo Mertoyudan Magelang. The method used for implementation of this activity was the method of community empowerment with the Participatory Rural Appraisal model, which is an approach method in the process of empowerment and increasing community participation, which is sensitive to community involvement in the overall activities carried out. The results of this service activity were carried out for five months, namely through the stages of preparation, counseling, training and mentoring. The results obtained were cadres who were able to practice using blood sugar levels and were able to detect hypoglycemia and hyperglycemia conditions. The range of early activities will be published in several mass media and community service journals. The conclusion are activity was achieved in view of the increased understanding and skills in carrying out the activity of checking blood sugar levels during and efforts to manage the increase in blood sugar levels / early detection of diabetes mellitus